The effect of the halal industry on the export of Indonesian halal products - Ivanna Sechan; Dwi Nur'aini Ihsan; Prilla Kurnia Ningsih (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — To analyze the influence of the halal industry on the development of exports of halal products in Indonesia.Method — The type of data used in this research is quantitative and from secondary data sources. The research data was obtained from data from the Ministry of Industry and the Ministry of Trade of the Republic of Indonesia in the form of reports on the halal industry in Indonesia and exports of halal products in Indonesia for the 2015–2021 period.Result — The results of this study indicate that the halal quality of food and beverages, including export activities, has a major impact that can boost the economy. Muslim fashion has not had much of an impact on Indonesia's halal export growth due to intense competition from other countries and a lack of domestic fashion designers. Halal pharmaceutical and cosmetic products have a major impact on expanding exports of Indonesian halal products. As a result, this industry has a great opportunity to enter the world's halal cosmetic and pharmaceutical industries.Contribution — The halal industry's potential can be maximized even further in order to boost export value and reserve foreign exchange, making it one of the forces boosting Indonesia's economic growth.